AL-BIIATU AL-LUGHAWIYYAH WAMAHAARAH AL-KALAAM (DIRASAH HAALIYAH) LITHULLAAB AL-‘IDAAD AL-LUGHAWII FII MA’HAD ‘ULUMUL ISLAMIYAH WAL ‘ARABIYYAH FII INDONESIA (LIPIA) LIL’AAMI AD-DIRAASII 2022 M - Usman (Program Studi Pendidikan Bahasa Arab, 2023)
Title of Thesis: Role of language environment in improving speaking skills (Student I,dad Al-lughowy, Indonesian Islamic and Arabic Sciences Institute, 2022). This is research to undestand and reveal the role of language environment in the success of learning speaking skills. Two sources of data in this study, the first primary data, were sourced from Student I'dad al-lughowy of the Islamic and Arabic Sciences Institute (LIPIA) Jakarta in 2022, as well as Lecturers, and Leader of the Department. The second data are sourced from library literature in the form of books, theses, papers, and academic journals related to this research. This is research uses a descriptive qualitative approach. The results of the concluded research that the language environment at LIPIA is a good environment because it is supported by native speaker teachers, students who are enthusiastic and active in speaking Arabic, are also supported by complete and adequate media and infrastructure. The role of the environment is very important in the success of learning speaking skills. This is in line with the opinion of Hadi Dauli who stated that the language environment is very important in the success of foreign language learning. In line with the opinion of Rusdi Ahmad Tuaiman, which states that the language environment is very influential on human speech skills